Obesity defined molecular endotypes in the synovium of patients with osteoarthritis provides a rationale for therapeutic targeting of fibroblast subsets. Issue 4 (3rd April 2023) - Wijesinghe, Susanne N.; Badoume, Amel; Nanus, Dominika E.; Sharma‐Oates, Archana; Farah, Hussein; Certo, Michelangelo; Alnajjar, Fawzeyah; Davis, Edward T.; Mauro, Claudio; Lindsay, Mark A.; Jones, Simon W.
Abstract: Background: Osteoarthritis (OA), a multifaceted condition, poses a significant challenge for the successful clinical development of therapeutics due to heterogeneity. However, classifying molecular endotypes of OA pathogenesis could provide invaluable phenotype‐directed routes for stratifying subgroups of patients for targeted therapeutics, leading to greater chances of success in trials. This study establishes endotypes in OA soft joint tissue driven by obesity in both load‐bearing and non‐load bearing joints. Methods: Hand, hip, knee and foot joint synovial tissue was obtained from OA patients ( n  = 32) classified as obese (BMI > 30) or normal weight (BMI 18.5–24.9). Isolated fibroblasts (OA SF) were assayed by Olink proteomic panel, seahorse metabolic flux assay, Illumina's NextSeq 500 bulk and Chromium 10X single cell RNA‐sequencing, validated by Luminex and immunofluorescence. Results: Targeted proteomic, metabolic and transcriptomic analysis found the inflammatory landscape of OA SFs are independently impacted by obesity, joint loading and anatomical site with significant heterogeneity between obese and normal weight patients, confirmed by bulk RNAseq. Further investigation by single cell RNAseq identified four functional molecular endotypes including obesity specific subsets defined by an inflammatory endotype related to immune cell regulation, fibroblast activation and inflammatory signaling, with up‐regulated CXCL12, CFD and CHI3L1 expression. Luminex confirmed elevated chitase3‐like‐1(229.5 vs. 49.5 ng/ml, p  < .05) and inhibin (20.6 vs. 63.8 pg/ml, p  < .05) in obese and normal weight OA SFs, respectively. Lastly, we find SF subsets in obese patients spatially localise in sublining and lining layers of OA synovium and can be distinguished by differential expression of the transcriptional regulators MYC and FOS. Conclusion: These findings demonstrate the significance of obesity in changing the inflammatory landscape of synovial fibroblasts in both load bearing and non‐load bearing joints. Describing multiple heterogeneous OA SF populations characterised by specific molecular endotypes, which drive heterogeneity in OA disease pathogenesis. These molecular endotypes may provide a route for the stratification of patients in clinical trials, providing a rational for the therapeutic targeting of specific SF subsets in specific patient populations with arthritic conditions. Abstract : The inflammatory landscape of OA synovial fibroblasts (SFs), from hand, hip, knee and foot joint synovial tissue, are independently impacted by obesity, joint loading, and anatomical site. Resulting in significant heterogeneity between obese and normal weight patients, due to the presence and predominance of specific SF subsets, which can be defined by four functional molecular endotypes.